Driving Factors of the Digital economy Under the Moderating Impact of Social Factors: Empirical Evidence from Vietnam - Nguyen, Nam Danh (Journal of Posthumanism, 2025)
In the context of the intense global wave of digitalization, with data and technology playing a leading role, the digital economy has become a key factor in the development of countries. The digital transformation process is accelerating to build a robust digital economy with global competitiveness in emerging markets like Vietnam. This research aims to identify the factors driving the digital economy in Vietnam. Using 355 survey samples and quantitative analysis methods such as reliability testing, exploratory factor analysis, correlation analysis, and MMR hierarchical regression analysis, combined with regulatory variable testing on the Macro Process. The results reveal that digital infrastructure, R&D and innovation, enterprise capacity, international economic integration, government policies, the market, and human capital have a direct impact on driving the digital economy in Vietnam. Furthermore, the findings demonstrate that social factors not only positively moderates the relationships between these factors and the digital economy but also directly impacts it. Based on these results, several implications are suggested to optimize existing potentials and further promote the development of the digital economy in Vietnam.